Postpartum Pneumomediastinum and Subcutaneous Emphysema: Two Case Reports - Shivanthi Kandiah; Harish Iswariah; Stephen Elgey (Hindawi Limited, 2013)
Spontaneous pneumomediastinum associated with subcutaneous emphysema is a rare condition also known as Hamman's syndrome. It can also be seen postpartum. We present two cases of subcutaneous emphysema associated with childbirth in nulliparous women, both of which resolved spontaneously.